Service experience on skin cares customer attitude: the mediating role of self-congruity and functional congruity - Kristiningsih Kristiningsih; Sri Hartini; Indrianawati Usman (BISMA (Bisnis dan Manajemen), 2020)
This paper aimed to provide empirical evidence of the relationship between service experience, self-congruity, functional congruity, and consumer attitude. The hypothesis in this study showed that service experience affected self-congruity and functional congruity which in turn will have an impact on consumer attitude. Data were collected through online surveys, on skin care consumer in East Java Indonesia. Hypotheses were tested using the structural equation modelling technique by WARP PLS. This paper validated the role of service experience as a mechanism facilitating the development of customer's self-congruity and functional congruity toward a skin care clinic. It also found that service experience affected in self-congruity and functional congruity, self-congruity, and functional congruity mediated the relationship between service experience and consumer attitude.